Religion and identity in modern Russia the revival of Orthodoxy and Islam - Forest, Benjamin; Johnson, Juliet Ellen 1968-; Stepanjanc, Mariėtta Tigranovna 1935- (Abingdon, Oxon Routledge, Taylor & Francis Group, 2016)
Religion after communism : belief, identity, and the Soviet legacy in Russia / Juliet Johnson -- Ethno-religious identity in modern Russia -- Orthodoxy and Islam compared / Marietta Stepaniants -- Orthodoxy, ethnicity, and mass ethnophobias in the late tsarist era / Liudmila Gatagova -- In search of the "Russian idea" : a view from inside the Russian Orthodox Church / Georgii Chistiakov -- Tolerance and extremism : Russian ethnicity in the Orthodox discourse of the 1990s / Svetlana Ryzhova -- Islam and the emergence of Tatar national identity / Aidar Yuzeev -- Islam and the construction of Tatar sociolinguistic identity / Suzanne Wertheim -- The search for ethnic and religious identity in Dagestan / Zagir Arukhov -- Modern identities in Russia : a new struggle for the soul? / Juliet Johnson
Includes bibliographical references and index. - Online resource; title from PDF title page (EBSCO, viewed March 10, 2017)
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Russkai︠a︡ pravoslavnai︠a︡ t︠s︡erkovʹ -- History -- 20th century -- Russkai︠a︡ pravoslavnai︠a︡ t︠s︡erkovʹ -- 1900-1999; Russkai︠a︡ pravoslavnai︠a︡ t︠s︡erkovʹ -- History -- 20th century; Russkai︠a︡ pravoslavnai︠a︡ t︠s︡erkovʹ; Islam -- History -- 20th century -- Russia; Nationalism -- Russia; Nationalism -- Russia; Identification (religion); Islam -- Russia -- History -- 20th century; RELIGION ; Christianity ; Orthodox; Church History; History; Nationalism; Islam; Russia -- Church history -- 20th century -- Russia; Russia -- Church history -- 20th century; Russia; Electronic books -- Church history -- History; Aufsatzsammlung